Real-Time Continuous Glucose Monitoring in Gestational Diabetes: A Randomized Controlled Trial - Lane, Andrew S.; Mlynarczyk, Malgorzata A.; de Veciana, Margarita; Green, Lauren M.; Baraki, Dana I.; Abuhamad, Alfred Z. (American Journal of Perinatology, 2019)
Objective To evaluate whether real-time continuous glucose monitoring improves glycemic control over intermittent self-monitoring of blood glucose in gestational diabetes.Study Design We performed a single-institution randomized controlled trial. Patients with gestational diabetes were randomized to use either real-time or blinded continuous glucose monitoring. The primary outcome was mean sensor glucose level during the fourth week of continuous glucose monitoring use. Secondary outcomes included glycemic control and a composite of obstetric and neonatal outcomes.Results Of the 40 enrolled patients, 12 (60%) patients in the blinded continuous glucose monitoring group and 11 (55%) in the real-time continuous glucose monitoring group completed 4 weeks of monitoring and were included in the final analysis. There was no significant difference in mean sensor glucose level between the blinded continuous glucose monitoring group (98.9 ± 8.9 mg/dL) and the real-time continuous glucose monitoring group (107.5 ± 11.4 mg/dL). There were also no significant differences in the time spent in glycemic target, maternal, or neonatal outcomes.Conclusion Our study shows that the use of continuous glucose monitoring with real-time feedback did not significantly decrease mean glucose values compared with intermittent self-monitoring of blood glucose after 4 weeks of continuous glucose monitoring use.
Keywords: gestational diabetes; diabetes; pregnancy; continuous glucose monitoring; glucose monitoring